A Critical Translation of Historical Texts (Torath) - Hojatallah Judaki (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Torath is said to be a collection of literary and historical heritage that has been inherited from our ancestors and naturally written with their condition. Throughout history, due to changes made in the language, sometimes writing has become different from generation to generation, and therefore it is difficult to understand the writings of the predecessors. The longer the text is older, the more difficult it is. In addition, the problem will be doubled when such texts should be translated. It is clear that all people cannot go to the original texts and have to use their translations. This is where the role of the translator as a mediator emerges. The translation will become more and more true and influent to the extent that the translator translates in a field that he has capability and has a mastery in the language of origin and destination.